Unlocking entrepreneurial potential: Key factors driving asnaf students into business - Abdull Rahman, Nurul Labanihuda; Abd Rahman, Hairulniza; Mhd Nasir, Nurul Farihin; Muhd Zailani, Nabilah Akemal; Abdul Pisal, Nadhilah (International Journal of Accounting, Finance and Business, 2026)
Entrepreneurship highlights the ability to start and manage businesses, which supports the overall economic development of a nation. It is a career path increasingly favoured by young people, particularly in developed countries. Nevertheless, previous studies have primarily focused on factors influencing the attitudes of Asnaf students in higher education toward entrepreneurship. This study aims to identify the factors that affect Asnaf students’ inclination to engage in entrepreneurial activities. Using a qualitative case study approach, the findings reveal that both internal and external factors such as personal trait, religious values, family support, financial access, environmental influences, and technological competence significantly shape students’ entrepreneurial tendencies. These factors enhance their motivation, creativity, management skills, and willingness to take risks. The findings suggest that mentorship programs, entrepreneurial education, and technology training will help Asnaf students develop their potential to become successful entrepreneurs and actively contribute to future economic development.